El comportamiento del precio de los productos agroecológicos y los niveles de consumo en la población de Riobamba - Arteaga Córdoba, Wladimir Santiago (2022)
The present research project contributed with new knowledge and guidelines of the level of variation of prices in agroecological products in the Riobamba city, to provide the basic tools that allowed the correct analysis of prices in consumers and pricing by producers, taking into consideration the different existing factors that generate a variant in the price in a constant way and therefore the fluctuations generate dissatisfaction in both entities. In this sense, within the research process, several socio-cultural and demographic characteristics have been included: sex, age, ethnicity and income level; these characteristics allow tracing the different behaviors to be analyzed in this research. Specifically, two issues related to the behavior of the price of agroecological products and the level of consumption analyzed, and to achieve this analysis and the development of the objectives, an empirical work has been developed based on a sample of 383 people, who have been divided into producers and consumers. The results obtained in this research have allowed us to draw a profile of price behavior and its variance in the market, as well as the implication of consumption levels by consumers.